Program Deradikalisasi Radikalisme dan Terorisme Melalui Nilai-Nilai Luhur Pancasila - Fuadi Isnawan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
Deradicalisation is every effort to neutralize radical ideals through interdisciplinary approaches, such as law, psychology, religion, economics, education, humanity and socio-culture for those who are influenced or exposed to radical and / or pro-violence. Implementation of Deradicalization Program (Development) can be done through Deradicalization in Prisons with the Target of terrorism prisoners who are in prison by identifying, Rehabilitation, Reeducation and Resosialisation. Deradicalisation has a goal, among other things, to restore the actors involved who have a radical understanding to return to a more moderate mindset. Deradicalisation of terrorism is very important because terrorism has become a serious problem for the international community because at any time it will endanger the national security for the country hence deradicalization program is needed as a formula of prevention and prevention of radical understanding like terrorism. Keywords: Deradicalisation, Terrorism, Development, Radicalism